Change in the spatiotemporal pattern of snowfall during the cold season under climate change in a snow‐dominated region of China. (28th June 2019) - Bai, Lei; Shi, Chunxiang; Shi, Qingdong; Li, Lanhai; Wu, Jing; Yang, Yanfen; Sun, Shuai; Zhang, Feiyun; Meng, Junyao
Abstract: The spatiotemporal pattern of precipitation is significantly changing with global climate change. Snowfall is a solid phase of precipitation and an important water resource. With two gridded data sets of APHRO (Asia Precipitation‐Highly‐Resolved Observational Data Integration Towards Evaluation of Water Resources) and CN05.1, this study analyses the changes in the spatiotemporal pattern of snowfall in a snow‐dominant region of China from 1961 to 2015. The results indicate the significant increasing trend of winter snowfall in horizontal and altitude dimension in snow‐dominant regions, but the winter snowing season length shortened. For the frequency of snowfall intensity level, light, and heavy snowfall and snowstorms increased, but moderate snowfall showed no change. However, the intensity of extreme snowfall in once‐in‐a‐century was decreasing in all of the snow‐dominant regions. In the altitude dimension, the increasing trend in snow‐dominant conditions was not uniform, which may be related to change in air temperature and water vapour through the vertical atmospheric levels. The upwards trend in snowfall may be caused by the increase of atmospheric water content rather than the change of snowy weather conditions. In addition, the change values of climate indices can also contribute to snowfall increasing in snow‐dominant regions. Abstract : Changes of spatiotemporal patterns of snowfall is analysed systematically. Multiple snowfall/rainfall partitioning methods and precipitation data sets are used. Frequency of snowfall intensity is increased with decreasing of extreme snowfall intensity. Upwards trend in snowfall may be caused by the increase of atmospheric water content.